Motivation As A Key Driver For Performance Improvement Among Health Promotion Staff At Jalan Gedang Health Centre, Bengkulu City - Mansyur, Edriwan; Salim, Muhartini; Abdillah, Willy; Praningrum (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2024)
This study explores the impact of motivation on the performance of health promotion staff at the Jalan Gedang Health Centre in Bengkulu City, addressing a gap in understanding the role of intrinsic and extrinsic motivators in public health contexts. Using a mixed-methods approach with quantitative surveys and qualitative interviews involving 50 staff members, the research aims to identify key motivational factors influencing performance. Results show that intrinsic motivation, such as personal growth and job satisfaction, and extrinsic factors, including recognition, incentives, and a supportive work environment, are significantly associated with enhanced performance. Staff who feel valued and supported demonstrate greater engagement, contributing to improved health outcomes in the community. The findings highlight the need for motivating work environments through leadership, recognition programs, and professional development, underscoring motivation’s potential to enhance service quality in public health.